2019
DOI: 10.1007/s10973-019-08187-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermal characterization of the effect of fillers and ionic liquids on the vulcanization and properties of acrylonitrile–butadiene elastomer

Abstract: Different thermal analysis techniques were used to study the effect of fillers and ionic liquids (ILs) on the vulcanization process, thermal and dynamic mechanical properties of acrylonitrile-butadiene elastomer (NBR). The products of the studies were composites of NBR filled with hydrotalcite, nanosized silica or carbon black. ILs such as 1-butyl-1-methylpyrrolidinium (BMpyrrolBF 4), 1-butyl-4-methylpyridinium (BMpyrBF 4) or 1-butyl-1-methylpiperidinium (BMpipBF 4) tetrafluoroborates were applied to improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
6
16
0
Order By: Relevance
“…As a result, it may have a positive effect on the cross-linking process. Vulcanization is more effective in an alkaline environment, thereby increasing the efficiency of the cross-linking system [ 33 ]. The silanization of the straw used as an active natural rubber additive contributed to the reduction of the process temperature by another few degrees Celsius.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, it may have a positive effect on the cross-linking process. Vulcanization is more effective in an alkaline environment, thereby increasing the efficiency of the cross-linking system [ 33 ]. The silanization of the straw used as an active natural rubber additive contributed to the reduction of the process temperature by another few degrees Celsius.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, application of pyrrolidinium and ammonium ILs with TFSI anion had a positive impact on the cure characteristics—they acted as coagents of vulcanization, whereas sulfonium ILs did not support the vulcanization of NR compounds, acting rather as vulcanization retarders. The positive impact of pyrrolidinium ILs on t 90 was confirmed by Maciejewska et al for NBR composites with different fillers [ 60 ], whereas Przybyszewska et al reported that alkylammonium salts shortened t 90 of unfilled NBR compounds [ 61 ].…”
Section: Resultsmentioning
confidence: 95%
“…It is known that the basic environment of this type of reaction accelerates the curing processes and influences the efficiency of cross-linking. In the case of a composite containing a filler, which includes montmorillonite modified with methyl dihydroxyethyl hydrogenated tallow ammonium, the effect of reducing the t 90 value could be the result of the quaternary ammonium compound acting as a surfactant [ 49 ], increasing the filler dispersion degree [ 50 ].…”
Section: Resultsmentioning
confidence: 99%